Analysis of the Factors Affecting the Financial Performance of Insurance Companies using Statistical Modeling - Younis A., Halima; Salem, Hamdy Mohamed; Alsanea, Mahmoud Selim; Elemam, Halla Z. S.; Abaker, Abdelgalal O. I. (PT Mattawang Mediatama Solution, 2025)
The insurance industry is fundamental to the global economy, accounting for about 7% of the gross domestic product (GDP) in numerous developed nations and serving a crucial function in risk management and financial stability. Recent years have seen escalating economic pressures that have adversely affected the profitability of insurance firms. These Difficulties encompass escalating inflation rates, a surge in claims, and losses attributable to natural disasters, with swings in interest rates that have impacted investment returns and the valuation of financial portfolios. This study aims to examine the determinants influencing the financial performance of insurance businesses through precise statistical models, with a particular emphasis on return on equity (ROE) as a principal metric. The research utilized real-time data encompassing characteristics such as insurance density, interest rates, underwriting capacity, and insurance expenditures, among others. Statistical modeling was employed to ensure the degree to which these factors influence profitability. The project seeks to establish an analytical framework to improve the efficiency of underwriting and pricing decisions. It further advances academic literature by utilizing sophisticated analytical tools to understand profitability dynamics inside the insurance sector.